Revision of the genus Nephelobotys Munroe & Mutuura, 1970 (Lepidoptera, Crambidae, Pyraustinae) - Zhang, Dandan; Chen, Kai; Xiang, Lanbin; Kou, Zongqing (Zootaxa, 2024)
The genus Nephelobotys Munroe & Mutuura, 1970 is revised to include eight species. Three species, N. apiculata sp. nov., N. semicircularis sp. nov. and N. brevis sp. nov. are described as new to science. Two new combinations, N. habisalis (Walker, 1859) comb. nov. and N. flavicilialis (Snellen, 1890) comb. nov., are proposed. N. forcipatus Ko & Bae, 2022 syn. nov. is found to be identical with N. habisalis (Walker, 1859). Diagnoses for all species are provided, with illustrations of external features and genitalia.